EFEKTIVITAS BADAN USAHA MILIK DESA (BUMDesa) DALAM MENINGKATKAN PEMBERDAYAAN MASYARAKAT DI DESA CIREUNDEU KECAMATAN CILOGRANG - Deden Rahmat; Aah Tsamrotul Fuadah; Utang Rosyidin (Mimbar Administrasi Mandiri, 2022)
BUMDesa “Tirta Kahuripan” is the only Cireundeu Village Owned Enterprise which was established in 2016. In running its business. BUMDesa “Tirta Kahuripan” Cireundeu Village is engaged in drinking water packaging. The choice of this form of business was motivated by the existence of abundant springs in Cireundeu Village which, if used by the community, could increase the economic value. It is hoped that by improving the community's economy, it can have an impact on the improvement and quality of life of the local community. The results of research on the management of BUMDesa "Tirta Kahuripan” in Cireundeu Village, Cilograng District in improving community empowerment have not been effective. It is known from 5 (five) dimensions, 4 (four) dimensions (80%) have not been effective, namely (1) the dimension of accuracy in the use of human resources can be said to have not been effective; (2) the dimensions of the accuracy of the use of equipment or equipment can be said to have not been effective; (3) The dimensions of the accuracy of the use of available time can be said to have not been effective; (4) the dimension of the accuracy of the use of natural resources can be said to have not been effective, while (5) the dimension of the accuracy of the use of the budget has been effective.